2014
DOI: 10.1007/s10266-013-0145-y
|View full text |Cite
|
Sign up to set email alerts
|

Cementogenic potential of multipotential mesenchymal stem cells purified from the human periodontal ligament

Abstract: The periodontal ligament (PDL) consists of a group of specialized connective tissue fibers embedded in the alveolar bone and cementum that are believed to contain progenitors for mineralized tissue-forming cell lineages. These progenitors may contribute to regenerative cell therapy or tissue engineering methods aimed at recovery of tissue formation and functions lost in periodontal degenerative changes. Some reports using immortal clonal cell lines of cementoblasts, which are cells containing mineralized tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…More importantly, in addition to the ability to differentiate into osteoblast-like cells and adipocytes, PDLSCs can also specifically differentiate into periodontal cells, such as cementoblast-like cells and collagen forming cells in vitro, and they possess the capacity to generate a cementum/PDL-like structure when they were transplanted into nude mouse and preclinical periodontal defect models. [5][6][7][8][9][10][11][12] Conventional hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 , HA) bioceramics had been used in periodontal bone tissue repair for their chemical similarity to bone mineral and their excellent biological activity and osteoconductivity. 13 However, it is reported that HA bioceramics lack osteoinductive ability, and consequently possess limited ability to form an interface with new bone tissue and hence hamper the new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, in addition to the ability to differentiate into osteoblast-like cells and adipocytes, PDLSCs can also specifically differentiate into periodontal cells, such as cementoblast-like cells and collagen forming cells in vitro, and they possess the capacity to generate a cementum/PDL-like structure when they were transplanted into nude mouse and preclinical periodontal defect models. [5][6][7][8][9][10][11][12] Conventional hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 , HA) bioceramics had been used in periodontal bone tissue repair for their chemical similarity to bone mineral and their excellent biological activity and osteoconductivity. 13 However, it is reported that HA bioceramics lack osteoinductive ability, and consequently possess limited ability to form an interface with new bone tissue and hence hamper the new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of application, DPSC have seen increasing use in the field of endodontics as regenerative treatment of pulpal necrosis of the permanent dentition, with studies indicating dentin-like tissue formation both in vitro and in mandibular defects [10] . Periodontal ligament stem cells (PDLSC) also demonstrates multipotency, with the most notable being osteogenesis and cementogenesis [29,30] . Interestingly, both its induction of nerve regeneration and angiogenesis contributes to its unique versatility in generating mature woven bone seen in healthy human tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the most defining characteristic of PDLSC is their multipotency, with the most well-studied being their ability to undergo osteogenesis and cementogenesis [29,30] . Further, PDLSC have been shown to be a viable, alternative source to autologous Schwann cells, in one instance promoting the regeneration of the mental nerve [31] .…”
Section: Background and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations